Busca de substâncias bioativas em plantas amazônicas: Adiscanthus fusciflorus (Rutaceae), Trichilia pallida e T. rubra (Meliaceae) - Rocha, Waldireny Caldas (2004)
The aim of this work was the search for antiparasitic and insecticide compounds in active extracts from the following amazon plants: A. fusciflorus (Rutaceae), T pallida e T. rubra (Meliaceae). The selected biological models were: 1) antiparasitic activity against the forms tripomastigota of T. cruzi, inhibition of the activity of gGAPDH of T. cruzi, inhibition of the activity of APRT of L. tarentolae and 2) insecticidal activity - against Spodoptera frugiperda and Atta sexdens a leafcutter ant. All the extracts were bioasseyed and liquid-liquid partition was carried out. From this each partition they were obtained five fractions that were obtained from each extract and these were assayed as well. The fractions were selected by two criteria: the) evaluation of the biological activity of the fractions in relation to your respective extracts and chemical profile of each fraction. Through successive fractioning it was possible to isolate and identify series of different compounds such as: dihydrocinnamic acid derivatives, coumarins, alkaloids, triterpenoids and steroids (some of them are described for the first time), limonoids and flavonoids. The identification of the compounds was carried out through different kind of NMR technique and comparison with data from the literature. The search for compounds with inhibitory activity on the enzyme APRT led to the furanoquinoline alkaloids. The results obtained for inhibitory effect of the enzyme gGAPDH of T. cruzi are promising compounds. Some of the isolated compounds showed interesting activity against trypomastigote forms of T. cruzi. The results obtained for inhibitory effect of the enzyme gGAPDH of T. cruzi are promising compounds. Some of the isolated compounds showed interesting activity against trypomastigote forms of T. cruzi. In the search for insecticidal compounds against S. frugiperda it was evaluated the activity of limonoids, cicloartane triterpenes, steroids, flavonoids, cumarins and alkaloids. Special attention was driven to the incorporation of skiamminine and the estimate DL50. In the bioassay carried out to A. sexdens it was observed the toxicity of some extracts, mainly the methanol extract of leaves from A. fusciflorus. It was also observed that some compounds exhibited antimicrobial activity on symbiotic fungi of A. sexdens and for some pathogenic bacteria. In conclusion, in this work it was possible to isolate and identify active compounds in all proposed biological models.